Dissemination of Piscine orthoreovirus-1 (PRV-1) in Atlantic Salmon (Salmo salar) during the Early and Regenerating Phases of Infection - Dhamotharan, Kannimuthu; Bjørgen, Håvard; Malik, Muhammad Salman; Nyman, Ingvild Berg; Markussen, Turhan Ali Dadasbilge; Dahle, Maria; Koppang, Erling Olaf; Wessel, Øystein; Rimstad, Espen (Pathogens, 2020)
Piscine orthoreovirus-1 (PRV-1) can cause heart and skeletal muscle inflammation (HSMI) in farmed Atlantic salmon ( Salmo salar ), but the line of events from infection, pathologic change, and regeneration has not been thoroughly described. In this study, the cellular localization and variation of PRV-1 RNA and protein levels were analyzed at different times post-exposure in experimentally infected Atlantic salmon. Immunohistochemistry, flow cytometry, and Western blot were used for assessment of the presence of the PRV-1 σ1 protein, while RT-qPCR and in situ hybridization were performed for viral RNA. Histopathologic evaluation demonstrated that PRV-1 infection induced heart lesions typical of HSMI, such as severe epicarditis and myocarditis with degeneration of cardiomyocytes, necrosis, and diffuse cellular infiltration. PRV-1 infection of erythrocytes and the peak viral plasma level preceded virus presence in cardiomyocytes and hepatocytes. Arginase-2-positive, macrophage-like cells observed in the heart indicated possible polarization to M2 macrophages and the onset of regenerative processes, which may contribute to the recovery from HSMI. The virus was cleared from regenerating heart tissue and from hepatocytes, but persisted in erythrocytes.